PENINGKATAN PROSES PEMBELAJARAN TEMATIK TERPADU MENGGUNAKAN PENDEKATAN SAINTIFIK SISWA KELAS III SEKOLAH DASAR - Zahratul Amalia; Riza Safriani; Delismita Pusra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
The purpose of this study was to improve integrated thematic learning process through scientific approach at grade 3 elementary school. The subjects of this study were researchers as the teachers, and 22 students. This study applied PTK research. This study utilized a qualitative and quantitative approach. The results showed an increase in: (a) the average value of RPP in cycle I for 98% (A) and 100% (A) in cycle II, (b) the result of the learning process from teachers' aspects in cycle I was 80% (B) and in cycle 2 was 95% (A), (c) the students' aspects in cycle 1 was 51.59% (D) and in cycle II was 86.59% (A).